Brief Notes: Aligned Magnetic Effects on the Flow Down an Open Inclined Channel with Highly Porous Bed - Chauhan, D.S.; Vyas, P. (Engineering Transactions, 1994)
The aligned magnetic effects on a steady, laminar, viscous, incompressible, conducting fluid flow down an open inclined rectangular channel, bounded below by a highly porous bed, have been studied. The Brinkman equation modified for MHD is assumed to govern the flow in the porous bed and a set of modified boundary conditions, taking into account the effective viscosity considerations, have been applied at the fluid-porous medium interface. The expressions for velocity distribution, magnetic strength and flux along the channel are obtained and discussed.